(untitled) (Journal of Health, Population and Nutrition, 2010)
The purpose of this commentary is to provide an overview of the growing interest in global health education at ICDDR,B and to review examples of how this has grown from public-health research and education to include clinical education (medical and nursing) as well. This parallels the growth of the institution, with an increased focus on educational linkages within and beyond Bangladesh and the rise in interest in global health at western medical schools. Specific collaborations, their setup and structure are described. This is presented as a model for other centres of excellence in developing countries to engage their partners in the South and North on matters of education and research for mutual cooperation and benefit. Key words: Collaborations; Health education; Public health DOI: 10.3329/jhpn.v28i6.6600 J HEALTH POPUL NUTR 2010 Dec;28(6):533-536